Halal Tourism in Aceh: Opportunities and Challenges - Khairil Umuri; Junia Farma; Eka Nurlina (Al Mashaadir : Jurnal Ilmu Syariah, 2022)
Halal tourism is an alternative in increasing the economy. Aceh is an area that has natural and cultural potential in the development of halal tourism. This study aims to analyze the potential and challenges of developing halal tourism in Aceh. Secondary data is used as the basis for obtaining qualitatively analyzed information. The results of the study indicate that there are several opportunities for developing halal tourism such as the majority of Acehnese are Muslim, the application of Islamic law, natural beauty and panoramas, interesting culture and history. In addition to opportunities, there are also challenges in the development of halal tourism, such as the lack of public understanding of the concept of halal awareness, geographical factors, demographic factors, factors of concern and seriousness from the government and the private sector, and infrastructure factors.